Wage Determination and Imperfect Competition - Alison L. Booth (Institute for the Study of Labor (IZA), 2014)
A striking feature of the past few decades has been the development of wage-determination models that assume that labour markets are imperfectly competitive. This paper discusses two such models (trade unions and oligopsony), although there are many more. It also asks if imperfectly competitive models should be used whenever researchers are modelling the labour market. Some people would argue for this only in cases when the predictions and comparative statics of the imperfectly competitive model differ from those of the competitive model. Of course, to know this, one needs to know precisely what the predictions and comparative statics of the respective models are. Moreover, for policymakers to be able to determine if an intervention is required in the first place, there does need to be some analytical framework to act as a guide. In the perfectly competitive model of the labour markets, for example, typically no intervention or regulation would be justified. However, labour economics has moved far beyond this position, with the incorporation of new ideas into modeling wage determination in imperfectly competitive labour markets, and with the availability of better datasets to facilitate empirical investigation.
Keywords: J2; J3; J5; D4; 330; wage determination; oligopsony; trade unions; imperfect competition; labour markets